2023
DOI: 10.1186/s12888-023-04867-w
|View full text |Cite
|
Sign up to set email alerts
|

Maternal distress and parenting during COVID-19: differential effects related to pre-pandemic distress?

Abstract: Background Distinguishing whether and how pre-existing characteristics impact maternal responses to adversity is difficult: Does prior well-being decrease the likelihood of encountering stressful experiences? Does it protect against adversity’s negative effects? We examine whether the interaction between relatively uniformly experienced adversity (due to COVID-19 experience) and individual variation in pre-existing (i.e., pre-pandemic onset) distress predicted mothers’ pandemic levels of distre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Given the nearly impossible task of simultaneously juggling work responsibilities with caring for children at home due to the closure of schools and childcare facilities, it is no wonder that many parents of young children experienced poor mental health (Kerr et al, 2021) and reported feelings of stress and exhaustion (Dawes et al, 2021) during the pandemic. Those particularly vulnerable to the pandemic have been high-conflict families (Low et al, 2023;Schmeer et al, 2023), families who employed harsh or inconsistent parenting (Ostrov et al, 2023), and families with children who were prone to anxiety (Tatsiopoulou et al, 2022) or stress (Ostrov et al, 2023).…”
Section: Gentle Parentingmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the nearly impossible task of simultaneously juggling work responsibilities with caring for children at home due to the closure of schools and childcare facilities, it is no wonder that many parents of young children experienced poor mental health (Kerr et al, 2021) and reported feelings of stress and exhaustion (Dawes et al, 2021) during the pandemic. Those particularly vulnerable to the pandemic have been high-conflict families (Low et al, 2023;Schmeer et al, 2023), families who employed harsh or inconsistent parenting (Ostrov et al, 2023), and families with children who were prone to anxiety (Tatsiopoulou et al, 2022) or stress (Ostrov et al, 2023).…”
Section: Gentle Parentingmentioning
confidence: 99%
“…Given the nearly impossible task of simultaneously juggling work responsibilities with caring for children at home due to the closure of schools and childcare facilities, it is no wonder that many parents of young children experienced poor mental health (Kerr et al, 2021) and reported feelings of stress and exhaustion (Dawes et al, 2021) during the pandemic. Those particularly vulnerable to the pandemic have been high-conflict families (Low et al, 2023;Schmeer et al, 2023), families who employed harsh or inconsistent parenting (Ostrov et al, 2023), and families with children who were prone to anxiety (Tatsiopoulou et al, 2022) or stress (Ostrov et al, 2023).Evidence suggests that even beyond the pandemic, the work of rearing children is simply seen as more stressful and difficult than it was in the past. A recent study within the United States by the Pew Research Center (2023) found that 41% of parents reported that being a parent is tiring, and 29% said it is stressful all or most of the time, with the youth mental health crises reported as a common concern among parents.…”
mentioning
confidence: 99%
“…Given the nearly impossible task of simultaneously juggling work responsibilities with caring for children at home due to the closure of schools and childcare facilities, it is no wonder that many parents of young children experienced poor mental health [ 5 ] and reported feelings of stress and exhaustion [ 6 ] during the pandemic. Those particularly vulnerable to the pandemic have been high-conflict families [ 1 , 7 ], families who employed harsh or inconsistent parenting [ 8 ], and families with children who were prone to stress or anxiety [ 9 ].…”
Section: Introductionmentioning
confidence: 99%